1986
DOI: 10.1111/j.1540-6288.1986.tb00719.x
|View full text |Cite
|
Sign up to set email alerts
|

Bank and Nonbank Credit Card Possession and Use: Changes Over Time

Abstract: University of Alabama P a t r i c i a M. Rudolph, University of Alabama Edward B. Selby, J r . , University of Georgia The possession and use of c r e d i t cards has been o f i n t e r e s t t o c r e d i t card i s s u e r s , monetary policy makers, and researchers f o r many years. Who possesses c r e d i t cards and how they are used has an impact on c r e d i t extension and the paymerit mechanism. Moreover, many of the sophisticated e l e c t r o n i c funds t r a n s f e r systems, such as point of s a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 0 publications
0
18
1
1
Order By: Relevance
“…Respondents' use of credit cards for day‐to‐day expenses and credit card spending on durables is low. Although previous studies found significant differences in making payments for household goods, clothing, entertainment, travel and food away from home by sex (see Lindley et al. , 1989; Hayhoe et al.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Respondents' use of credit cards for day‐to‐day expenses and credit card spending on durables is low. Although previous studies found significant differences in making payments for household goods, clothing, entertainment, travel and food away from home by sex (see Lindley et al. , 1989; Hayhoe et al.…”
Section: Discussionmentioning
confidence: 95%
“…, 1977); single males were more likely to use credit cards than females (White, 1975). Evidence also reveals that the impact of sex on types of credit card purchase is significant, where females use credit cards more for household goods, clothing and personal belongings (Lindley et al. , 1989; Hayhoe et al.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Much of the literature on credit card usage practices examined the type of credit card purchases (e.g. Lindley et al ., 1989; Hayhoe et al ., 2000; Kaynak and Harcar, 2001), the place of purchase (e.g. Hayhoe et al ., 2000; Kaynak and Harcar, 2001), credit history (Kim et al ., 2005) and the amount of monthly expenses through credit cards (Kaynak and Harcar, 2001).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Hayhoe et al ., 2000; Kaynak and Harcar, 2001), credit history (Kim et al ., 2005) and the amount of monthly expenses through credit cards (Kaynak and Harcar, 2001). For instance, past studies provide evidence that females use credit cards more for household goods, clothing and personal belongings (Lindley et al ., 1989; Hayhoe et al ., 2000; Kaynak and Harcar, 2001), while males use cards more for electronics, entertainment, travel and food away from home (Kaynak et al ., 1995; Hayhoe et al ., 2000; Kaynak and Harcar, 2001).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Ada juga yang menggunakan untuk membiayai konsumsi mereka (Lee & Kwon, 2002). Berbagai macam motif ini mendorong setiap pemegang KK memiliki perilaku yang berbeda seperti intensitas penggunaan (Chan, 1997), di mana KK sering digunakan, produk-produk tertentu yang dibeli (Lindley et al 1989). Kaynak & Harcar (2001) menemukan bahwa penggunaan KK berhubungan positif dengan pendidikan dan pendapatan.…”
Section: Penggunaan Kkunclassified